2020
DOI: 10.3389/fphar.2020.580251
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of CDK4/6 Inhibitor Resistance in Luminal Breast Cancer

Abstract: As a new-generation CDK inhibitor, a CDK4/6 inhibitor combined with endocrine therapy has been successful in the treatment of advanced estrogen receptor–positive (ER+) breast cancer. Although there has been overall progress in the treatment of cancer, drug resistance is an emerging cause for breast cancer–related death. Overcoming CDK4/6 resistance is an urgent problem. Overactivation of the cyclin-CDK-Rb axis related to uncontrolled cell proliferation is the main cause of CDK4/6 inhibitor resistance; however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 113 publications
1
39
0
Order By: Relevance
“…Some studies have considered the efficacy of Olaparib in ATM -deficient leukemic cells from patients with leukemia [ 68 ] or in patients with gastric cancer [ 69 ], but no studies in BC tumor cells have yet been performed. The ATM -dependent pathway is also involved in resistance to treatment with CDK4/6 inhibitors, recently introduced in clinical practice for the treatment of advanced estrogen receptor-positive BC [ 70 ]. In this regard, a recent study showed that defects in single-strand break repair in luminal BC can drive endocrine therapy resistance and are closely associated with the ATM-CHK2-CDC25A pathway.…”
Section: Therapeutic Implications Of Atm Gene Mutations In Bcmentioning
confidence: 99%
“…Some studies have considered the efficacy of Olaparib in ATM -deficient leukemic cells from patients with leukemia [ 68 ] or in patients with gastric cancer [ 69 ], but no studies in BC tumor cells have yet been performed. The ATM -dependent pathway is also involved in resistance to treatment with CDK4/6 inhibitors, recently introduced in clinical practice for the treatment of advanced estrogen receptor-positive BC [ 70 ]. In this regard, a recent study showed that defects in single-strand break repair in luminal BC can drive endocrine therapy resistance and are closely associated with the ATM-CHK2-CDC25A pathway.…”
Section: Therapeutic Implications Of Atm Gene Mutations In Bcmentioning
confidence: 99%
“…Endocrine therapies remain the best option for ER+ patients (luminal cancers), but the development of drug resistance is problematic. Patients can also develop resistance to CDK4 inhibitors (25), three of which are approved for clinical use (26). Identifying new targetable oncogenes will advance knowledge on the evolution and progression of cancer and reveal novel treatment approaches that improve the prognosis and long-term survival of cancer patients, especially those that develop resistance to front-line therapies.…”
Section: Introductionmentioning
confidence: 99%
“…All these drugs are already clinically available. In addition, data from other cancer types suggest several more putative mechanisms of resistance [60]: CDK4/6 overexpression [61], p16 amplification [62,63], upregulation of FGFR pathway [64,65], alteration of Hippo pathway [66], activation of CDK2 [67,68], autophagy [69], and epigenetic alterations [70,71].…”
Section: Resistance Mechanisms To Cdk4/6 Inhibitorsmentioning
confidence: 99%